Studies in law, politics, and society. - Sarat, Austin (Studies in law, politics, and society., 2015)
"The articles in this volume of Studies in law, politics, and society cover an exciting and diverse range of topics relating to laws relationship with and impact on society. Two articles cover immigration, but from very different perspectives. One examines the legal-cultural attitude of immigrants from the former Soviet Union to Israel while the other investigates US Immigration Policy and the notion of child saving. Other articles cover the institutional dynamics of same-sex marriage debates in America; the anti-strip mining movement in central Appalachia; an analysis of the death penalty in Maricopa County, Arizona, one of the most active death penalty locales in the contemporary U.S; and affirmative defenses at the International Criminal Court."